VARIABILITY IN EVALUATION AND TREATMENT OF PEDIATRIC TIBIAL TUBERCLE FRACTURES AMONGST PEDIATRIC ORTHOPAEDIC SURGEONS - Fields, Michael W. (Orthop J Sports Med, 2021)
INTRODUCTION: Tibial tubercle fractures are uncommon injuries typically seen in adolescents approaching skeletal maturity. No evidence based clinical practice guidelines currently exist regarding clinical management of both operative and nonoperative fractures. PURPOSE: To determine the variability in clinical management of tibial tubercle fractures among a group of pediatric orthopaedic surgeons. METHODS: Nine fellowship trained academic pediatric orthopaedic surgeons reviewed 51 anteroposterior and lateral knee radiographs with associated case age (mean: 13.6yrs, range: 9-16yrs) and gender (86%male). Respondents were asked to describe each fracture using the Ogden classification (Type 1-5 with A/B modifiers), desired radiographic workup, operative vs. nonoperative treatment strategy, and plans for post treatment follow-up. Interrater reliability was determined among the surgeons using Fleiss Kappa analysis. RESULTS: Fair agreement was reached when classifying the fracture type using the Ogden classification (k=0.39,p<0.001). There was slight agreement when determining if CT (k=0.10,p<0.001) should be ordered and when rating concern for compartment syndrome (k=0.17,p<0.001). Overall, surgeons had moderate agreement on whether to treat the fractures operatively vs. nonoperatively (k=0.51,p<0.001). Nonoperative management was selected for 80.4%(45/56) of Type 1A fractures. Respondents selected operative treatment for 75% (30/40) of Type 1B, 58.3% (14/24) of Type 2A, 97.4%(74/76) of Type 2B, 90.7%(39/43) of Type 3A, 96.3%(79/82) of Type 3B, 71.9%(87/121) of Type 4, and 94.1%(16/17) of Type 5 fractures. Regarding operative treatment, moderate agreement was reached when evaluating the emergent nature of the fracture (k=0.44,p<0.001) and surgical technique (k=0.44, p<0.001). However, only fair/slight agreement was reached when selecting the specifics of operative treatment including surgical fixation technique (k=0.25,p<0.001), screw type (k=0.26, p<0.001), screw size (k=0.08,p<0.001), use of washers (k=0.21,p<0.001), and performing a prophylactic anterior compartment fasciotomy (k=0.20,p<0.001). There was moderate agreement on radiographic work up at first (k=0.5,p<0.0011) and final (k=0.49,p<0.001) follow up visits. Surgeons had moderate agreement on plans to remove hardware (k=0.39,p<0.001). Non-operative treatment of fractures was observed to have only fair agreement (k=0.29,p<0.001). Furthermore, surgeons had fair/moderate agreement regarding the specifics of nonoperative treatment including degree of knee extension during immobilization (k=0.46,p<0.001), length of immobilization (k=0.34,p<0.001), post treatment weight bearing status (k=0.30,p<0.001), and post treatment rehabilitation (k=0.34,p<0.001). Finally, there was moderate agreement on radiographic work up at first (k=0.51,p<0.001) and final follow up (k=0.46,p<0.001). CONCLUSION: Significant variability exists between surgeons when evaluating and treating pediatric tibial tubercle fractures. Future studies should aim to create best practice guidelines for pediatric orthopaedic surgeons to reference when treating these fractures.